2016
DOI: 10.1111/fcp.12210
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of slow‐release morphine sulfate abuse and diversion: epidemiological approaches in a French administrative area

Abstract: Slow-release oral morphine sulfate (SM) is one of the most abused prescription opioids in France. However, the regional feature of the abuse of morphine is poorly documented. To investigate the abuse of SM in a French administrative region, a multisource approach was applied. The first approach was based on SM exposition at national and regional level using the OPPIDUM survey. In a second approach, we analyzed a drug reimbursement database to assess the magnitude of SM abuse in Languedoc-Roussillon (LR) region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…Indeed, in this subpopulation, a non-negligible proportion of adults resorted to the IR formulation, which has already been linked to diversion [1]. They also used flunitrazepam (24%) or morphine sulphate (22%), which are both potential drugs of abuse [54,55], and visited a larger number of different physicians, reinforcing the hypothesis of a possible diversion of MPH by 'doctor shopping', which consists of obtaining overlapping prescriptions by two or more prescribers [56]. This behaviour has, in particular, already been characterized in the PACA-Corse region (the same geographical region as investigated in our study), with an estimated increase of 6% in the overall quantities of MPH obtained by diversion through doctor shopping in 2011 [1].…”
Section: Bzd Benzodiazepinesmentioning
confidence: 99%
“…Indeed, in this subpopulation, a non-negligible proportion of adults resorted to the IR formulation, which has already been linked to diversion [1]. They also used flunitrazepam (24%) or morphine sulphate (22%), which are both potential drugs of abuse [54,55], and visited a larger number of different physicians, reinforcing the hypothesis of a possible diversion of MPH by 'doctor shopping', which consists of obtaining overlapping prescriptions by two or more prescribers [56]. This behaviour has, in particular, already been characterized in the PACA-Corse region (the same geographical region as investigated in our study), with an estimated increase of 6% in the overall quantities of MPH obtained by diversion through doctor shopping in 2011 [1].…”
Section: Bzd Benzodiazepinesmentioning
confidence: 99%
“…In Austria, Heroin was the main cause of opioid-related deaths [2,3,28] until the use of slow-release oral morphine became commonplace as drug substitution medication, and became the most frequently abused opiate during the early 2000s [29][30][31][32]. Although originally intended to be orally consumed, substance abuse involving slow-release oral morphine involves it being injected after the morphine has been extracted by crushing and heating [33][34][35][36][37]. Moreover, polydrug abuse is a widespread problem given that most opioid addicts consume additional substances, especially other central nervous system depressants such as alcohol and/or benzodiazepines [38][39][40]-all of them increasing the risk of a potentially fatal side effect of opioids such a respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…The PrebupIV survey (Roux et al, 2017) showed that morphine sulfate was used to get high more frequently than methadone and buprenorphine. Another French survey investigating this substance reported that 77.6% of users were searching for a rewarding effect (Peyriere et al, 2016).…”
Section: 0discussionmentioning
confidence: 99%